Desenvolvimento, e, caracterização de uma bebida não fermentada visando a valoração de frutos do estado do Amazonas. - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The Amazon forest is rich in species biodiversity, being a great source of natural products with nutritional and therapeutic properties. In the Brazilian Amazon, there are around 220 edible fruits produced by plant species, representing 44% of Brazil's fruit diversity, with great potential for the development of new products. Pouteria elegans (A.DC.) Baehni (Sapotaceae), an edible Amazonian fruit, popularly known as caramuri, yellow in color, white pulp and sweet flavor, is a fruit whose commercial and technological value has not yet been explored. One of the industrial segments where the fruits can be used is in the production of juices, nectar and blends. The fruit-based beverage market has shown signs of national and international expansion. The objective of this project was to obtain an unfermented drink from the fruits of P. elegans with the aim of revealing the food profile, in addition to the aromatic and physical-chemical characteristics present in the drink. Concerning the methodology adopted to complete the dissertation, analyzes of proximate, mineral and colorimetric composition, levels of organic acids (malic, citric and ascorbic) were carried out, evaluation of volatile organic compounds by solid phase micro extraction and analysis of the microbiological activity of the nectar. Six formulations were prepared with different pulp concentrations (30, 35 and 40%) and analyzed in groups containing different sugar concentrations (1.5, 2.5 and 3.5%). Caramuri nectar is low in calories (7.82 and 21.44 kcal/100g), with a moderate carbohydrate content (0.46 and 3.39 g/100g) and a high moisture content > 95%. The results obtained indicated low protein content (0.0 to 0.80 g/100g), and lipid content (0.40 to 1g /100g), acidic pH (4.45 to 4.55), and flavor slightly sweet (1.43 to 6.40 ͦ Brix). Of the minerals evaluated, a high potassium content (27.25 and 31.44 mg/100g) and a low sodium content (0.13 to 0.18/100g) were observed. The chromatographic analysis of volatile organic compounds in the fruit pulp at different stages of maturation showed trans-β-caryophyllene as the main substance identified in both samples. There were 22 volatile compounds found in the nectar divided between the groups terpenes, alkanes, esters and alkanes. The microbiological evaluation of the nectar showed that the samples met the standards required by current legislation. Therefore, the Caramuri fruit, through the results obtained, has the potential to serve as a raw material for the production of a new flavor in the preparation of drinks, such as nectar, made from fruits.
Development and characterization of a non-fermented beverage aiming at the valorization of fruits from the state of Amazonas.
Keywords: Compostos orgânicos - Amazônia; Análise cromatográfica; CIENCIAS EXATAS E DA TERRA; CIENCIAS BIOLOGICAS; Pouteria elegans; Néctar; Composição centesimal; Análise cromatográfica; Compostos orgânicos voláteis